Long-term use of modern Portland cement concrete: The impact of Al-tobermorite formation. (15th January 2021) - Maruyama, Ippei; Rymeš, Jiří; Aili, Abudushalamu; Sawada, Shohei; Kontani, Osamu; Ueda, Shinya; Shimamoto, Ryu
Abstract: The distribution of compressive strength in thick concrete members exposed to various environments in a nuclear power plant undergoing decommissioning is investigated. X-ray diffraction data, scanning electron microscopy analysis, and chemical analysis data reveal that rock-forming minerals in the aggregate had reacted and portlandite had been consumed to form calcium alumino silicate hydrates (C-A-S-H) when evaporable water content was sufficient. In addition, the study confirms Al-tobermorite formation in modern concrete after 16.5 years of elevated temperature conditions ranging from 40 to 55 °C. It is concluded that an appropriate aggregate and binder combination for the concrete enhances the compressive strength of thick concrete members thanks to the reaction of rock-forming minerals with portlandite, and also strengthens the chemical stability through the formation of Al-tobermorite under elevated temperature conditions and sufficient evaporable water content. Graphical abstract: Unlabelled Image Highlights: The first detailed investigation results of concrete from a commercial NPP 47 years after construction are presented. Al-tobermorite formation in modern Portland cement concrete in service was confirmed. Reaction between aggregate and cement hydrates produced C-A-S-H and Al-tobermorite. The reaction developed the strength of concrete dramatically.